2004
DOI: 10.1051/0004-6361:20041209
|View full text |Cite
|
Sign up to set email alerts
|

Multiple protostellar systems

Abstract: Abstract. We performed a deep infrared imaging survey of 63 embedded young stellar objects (YSOs) located in the Taurus and Ophiuchus clouds to search for companions. The sample includes Class I and flat infrared spectrum protostellar objects. We find 17 companions physically bound to 15 YSOs with angular separations in the range 0.8-10 (110-1400 AU) and derive a companion star fraction of 23 ± 9% and 29 ± 7% for embedded YSOs in Taurus and Ophiuchus, respectively, about twice as large as that found among G dw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 51 publications
11
147
1
Order By: Relevance
“…Many of the 154 M4+ TBOSS sample have been observed by infrared direct imaging from the ground (Duchêne et al 2004;Luhman et al 2009a), high resolution imaging employing spacebased measurements with HST (White & Ghez 2001;Kraus et al 2006;Todorov et al 2014), ground-based speckle imaging (Kohler & Leinert 1998;Konopacky et al 2007), and aperture masking or AO imaging (Kraus & Hillenbrand 2009b;Kraus et al 2011). The results of the PACS observations presented here therefore provide the opportunity to assess the similarity or difference in the frequency or typical flux density level of disks for targets with and without companions.…”
Section: Impact Of Companionsmentioning
confidence: 94%
See 2 more Smart Citations
“…Many of the 154 M4+ TBOSS sample have been observed by infrared direct imaging from the ground (Duchêne et al 2004;Luhman et al 2009a), high resolution imaging employing spacebased measurements with HST (White & Ghez 2001;Kraus et al 2006;Todorov et al 2014), ground-based speckle imaging (Kohler & Leinert 1998;Konopacky et al 2007), and aperture masking or AO imaging (Kraus & Hillenbrand 2009b;Kraus et al 2011). The results of the PACS observations presented here therefore provide the opportunity to assess the similarity or difference in the frequency or typical flux density level of disks for targets with and without companions.…”
Section: Impact Of Companionsmentioning
confidence: 94%
“…For the multiple systems with angular separations in the range ∼5-11 -FU Tau A+B, GG Tau Ba+Bb, IRAS 04191+1523 A+B, and IRAS 04325+2402 AB+C (Luhman et al 2009b;Duchêne et al 2004) -emission longward of the mid-IR is unresolved. For these systems, the combined system photometry were compiled, and the underlying best-fit spectra displayed on the SEDs was combined from the spectral types of both the primary and secondary components.…”
Section: Construction Of Spectral Energy Distributionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, extremely young protostars (i.e., Class 0 protostars) have been observed with radio interferometers (e.g., Looney et al 2000) and wide-field near-infrared cameras (Duchêne et al 2004). These observations showed that stars already have a high multiplicity at the moment of their birth.…”
Section: Fragmentation and Binary Formationmentioning
confidence: 99%
“…It is certainly the best target presently accessible from the ground to measure, for the first time, internal stellar motions in an embedded IR cluster. In addition, we can use various surveys that have studied this cluster (Bontemps et al 1998;Duchêne et al 2004;Stamatellos et al 2007), which have achieved a census of the population of young stars with IR excesses. This allowed these authors to discuss, for the first time, the mass function in such a young cluster down to masses of less than 0.1 M .…”
mentioning
confidence: 99%